Determining and modelling the effective period of fungicides against septoria leaf blotch in winter wheat. (March 2019) - Greiner, S.D.; Racca, P.; Jung, J.; von Tiedemann, A.
Abstract: The aim of this work was to develop a model to predict the effective period of fungicides for control of Zymoseptoria tritici (septoria leaf blotch) in winter wheat. Efficacy and duration of fungicidal effects of three fungicides, namely Bravo 500 (chlorothalonil), Epoxion (epoxiconazole), Imbrex (fluxapyroxad) and a mixture of Epoxion + Imbrex, were examined under field and laboratory conditions. In order to design a simulation model, a method for calculating the effective period of fungicides was developed. Key feature of this method is the comparison of disease progress curves on treated and untreated plants, based on data recorded in field trials. The effective period was considered to end when, after a prior fungicide application, rates of disease progress on treated and untreated plants became equal again. The effective periods of fungicides were calculated by subtracting latency periods of Z. tritici from the time point of recovery of maximum disease progress and lay between 16 and 22 days, depending on the fungicide. These findings were confirmed by fungicide residue analyses at the calculated time of expired fungicide efficacy where 3–44% of the initially applied doses of active substance were detectable. Based on calculations from field trials, a model to predict the fungicide effective periods was developed for field-grown winter wheat. Air temperature, precipitation and, depending on the fungicide, relative humidity were identified to be significant determinants of fungicide efficacy and effective periods. The validation confirmed the reliable prediction of the effective period of fungicides and a corresponding model named OPTIFUNG was developed. OPTIFUNG will be integrated in the wheat disease decision support model SEPTRI in order to optimize the timing and frequency of fungicide applications against septoria leaf blotch by including fungicide effective periods. As the method is based on general epidemiological principles, it may be useful for and is adaptable to yet any other leaf diseases in cereals which require sequential sprays with fungicides. Highlights: The effective period of fungicides applied in the field can be calculated. Calculation based on comparison of disease progress on untreated and treated plants. Weather parameters are significant determinants of fungicide effective periods. A basic approach has been developed and validated for leaf diseases in wheat. The model can be transferred to other crops and diseases.